Evaluation of GeneXpert vanA/vanB in the early diagnosis of vancomycin-resistant enterococci infection. - Zhuo-Lei Li; Qi-Bing Luo; Shan-Shan Xiao; Ze-Hong Lin; Ye-Ling Liu; Meng-Yi Han; Jing-Hua Zhong; Tian-Xing Ji; Xu-Guang Guo (Public Library of Science (PLoS), 2021)
Purpose Vancomycin-resistant enterococci infection is a worrying worldwide clinical problem. To evaluate the accuracy of GeneXpert vanA/vanB in the diagnosis of VRE, we conducted a systematic review in the study. Methods Experimental data were extracted from publications until May 03 2021 related to the diagnostic accuracy of GeneXpert vanA/vanB for VRE in PubMed, Embase, Web of Science and the Cochrane Library. The accuracy of GeneXpert vanA/vanB for VRE was evaluated using summary receiver to operate characteristic curve, pooled sensitivity, pooled specificity, positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio. Results 8 publications were divided into 3 groups according to two golden standard references, vanA and vanB group, vanA group, vanB group, including 6 researches, 5 researches and 5 researches, respectively. The pooled sensitivity and specificity of group vanA and vanB were 0.96 (95% CI, 0.93-0.98) and 0.90 (95% CI, 0.88-0.91) respectively. The DOR was 440.77 (95% CI, 37.92-5123.55). The pooled sensitivity and specificity of group vanA were 0.86 (95% CI, 0.81-0.90) and 0.99 (95% CI, 0.99-0.99) respectively, and those of group vanB were 0.85 (95% CI, 0.63-0.97) and 0.82 (95% CI, 0.80-0.83) respectively. Conclusion GeneXpert vanA/vanB can diagnose VRE with high-accuracy and shows greater accuracy in diagnosing vanA.